PESAN EDUKASI VAKSIN COVID-19 PADA INSTAGRAM @LAWANCOVID19_ID DAN TINGKAT KEPERCAYAAN FOLLOWERS - Putri Inatisya, (2021)
The decrease in data on the level of trust in vaccines based on the results of a survey conducted by Saifulmujani is one of the factors that must be a concern for the government, in this case the Ministry of Health and other institutions appointed as institutions for dealing with the COVID-19 pandemic, especially in the success of the vaccine program through education to the public. KPC PEN and the Satuan Tugas Penanganan Covid 19 manage Instagram @lawancovid19_id as a medium for educating things about covid-19, especially the covid-19 vaccine. This study aims to prove the effect of the COVID-19 vaccine education message on Instagram @lawancovid19_id on the level of trust. The method used is an explanatory survey with a sample of 100 from a population of 64,000 Instagram followers @lawancovid19_id as of March 31, 2021, using a purposive sample. Health communication as a theory is tested with the concept of educational messages and the level of trust in the covid-19 vaccine. The results show that the educational message for the covid-19 vaccine affects the level of trust. In conclusion, based on the results of the regression test and hypothesis testing, there is a real influence between the covid-19 vaccine education message on the level of trust of followers. Suggestions in this study, the covid-19 vaccine content on Instagram @lawancovid19_id is expected to be able to attract more viewers with content that adds to the audience's experience so that the message conveyed on the content can be more memorable to the communicant. It is also recommended to test on a larger and representative sample of various provinces.